Chinese Bridge online contest for the first time - UMP, PNC (2020)
Kuantan, 30 May 2020 - For the first time the Universiti Malaysia Pahang Confucius Institute (CI UMP) hosted the UMP Level Chinese Bridge Competition online using Zoom this year following the COVID-19 Pandemic which hit many countries today.